The migration intentions of international students non-Arabic speakers at King Abdul Aziz University: their characteristics and their spatial preferences (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to examine the migration intentions of international students at King Abdul Aziz University. Specifically, spatial preferences and the infancy of demographic and socioeconomic characteristics in the intention to migrate were examined. A sample of 200 international students was drawn representing 26 non-Arab countries from three continents. Using the inductive-deductive approach framework, about 57% of the sample participants desired to return to their home countries, 61% of which enrolled in humanities programs. For this group, the primary motivation behind their decision to return to their home country was disseminating the Arabic language and the rules of moderate Islamic law. However, when the chance emerged to access better employment opportunities, most of the sample participants expressed a preference for remaining in the Kingdom of Saudi Arabia or immigrating to another country. The study concluded with several key recommendations, including re-evaluating the admission process for international students based on geographical locations, offering scholarships for South American students along with expanding admission in the humanities and Islamic programs
Keywords: king Abdul Aziz university; international student; immigration; intentions; preferences